A “SIGN” OF THE TIMES: A BRIEF CONSIDERATION OF THE VALIDITY OF E-SIGNATURES IN AGREEMENTS AND AFFIDAVITS IN SOUTH AFRICAN LAW - Ciresh Singh (Obiter, 2024)
The evolution of technology has changed business practices all over the world. Owing to technological and e-commerce developments, businesses can now transact with each other instantaneously across borders. The digitalisation of commerce and other traditional working methods has created a new “digital age” in human history. Digitalisation has taken over many economic activities and industries and is slowly finding its way into the legal system. Several businesses are now concluding commercial transactions and contracts electronically. Electronic signatures have consequently become essential tools for concluding legal agreements and conducting other daily business and legal practices. These new innovations have brought into question the legal validly of these transactions, and in particular the legitimacy and security of electronically signed documents.